Bismuth oxide nanoparticles influence on ROS generation by targeted and bystander cells under Proton beam irradiation - Ab Rashid, Raizulnasuha; Sisin, Noor Nabilah Talik; Mohd Zainudin, Nur Hamizah; Razak, Khairunisak Abdul; Geso, Moshi; Akasaka, Hiroaki; Sasaki, Ryohei; Tominaga, Takahiro; Rahman, Wan Nordiana; Miura, Hayato (Sciendo, 2025)
Introduction: The goals of radiotherapy to achieve a therapeutic dose for the cancer cells and lower the dose for the surrounding healthy tissues might be possible with highly localized proton beam therapy. The lethal effects can further be increased by using nanomaterials as a radiosensitizer. Material and methods: In this study, the effects of bismuth oxide nanoparticles (BiONPs) in combination with a proton beam on the targeted and bystander cells were investigated by measuring the level of reactive oxygen species (ROS) generated. Human colon carcinoma cells (HCT 116) were incubated with 0.5 mM of BiONPs and then were exposed to 150 MeV proton beams with doses of 2 to 12 Gy at the dose rate of 0.1 Gy/s in a single fraction. ROS was measured for targeted cells after irradiation, and the effect on the bystander cells was measured using irradiated cell-conditioned medium (ICCM) with and without BiONPs. Results: The results show an increase in the ROS generation for irradiated cells treated with BiONPs. Meanwhile in bystander cells, the results indicated the increment in the ROS generation for cells with BiONPs ICCM compared to those with ICCM only. Nevertheless, the population means difference in ROS levels among bystander cells at different incubation times is insignificant (p<0.05). The bystander cells treated with ICCM @ 12 Gy also did not significantly differ from unirradiated cells with BiONPs ICCM @ 0 Gy (p<0.05). Conclusion: The application of BiONPs as a radiosensitizer in combination with proton beam therapy could improve tumor control with minimal risk of normal tissue complication.